2006
DOI: 10.1007/s11524-005-9022-5
|View full text |Cite
|
Sign up to set email alerts
|

Gun Carrying and Drug Selling Among Young Incarcerated Men and Women

Abstract: This paper examines the relationship between illegal drug economy involvement, gun-related victimization, and recent gun carrying among young men and women incarcerated in a state prison in the United States. Interviews were conducted with 18-to 25-year old incarcerated men (n = 135) and women (n = 69) between July 1999 and October 2000. Forty-five percent of men and 16% of women reported carrying a gun in the year prior to incarceration. Respondents who sold crack cocaine or other drugs were more likely to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Black and Ricardo (1994) find statistically significant correlations between weapon carrying, drug use, and drug trafficking. By comparison, Kacanek and Hemenway (2006) found that hard drug use was only associated with gun carrying among their female respondents. Despite these disparate findings, we find a remarkably high correlation between respondents who use and sell drugs or alcohol.…”
Section: (Continued)mentioning
confidence: 86%
“…Black and Ricardo (1994) find statistically significant correlations between weapon carrying, drug use, and drug trafficking. By comparison, Kacanek and Hemenway (2006) found that hard drug use was only associated with gun carrying among their female respondents. Despite these disparate findings, we find a remarkably high correlation between respondents who use and sell drugs or alcohol.…”
Section: (Continued)mentioning
confidence: 86%
“…For instance, 45 percent of the young adult men in the Kacanek and Hemenway (2006) sample reported carrying a gun in the six months prior to their incarceration and 24 percent of the inmates in the Sheley and Wright (1995) sample reported carrying a gun “all the time” in the two years prior to the incarceration.…”
Section: Notesmentioning
confidence: 99%
“…Public gun carrying may increase the chances that individuals will act on crime opportunities, such as vulnerable robbery targets (Kleck, 1991). In addition, survey evidence from different adult and juvenile samples of offenders show that important percentages have reported carrying firearms (Kacanek and Hemenway, 2006; May and Jarjoura, 2006; Sheley and Wright, 1995; Wright and Rossi, 1986)[1].…”
Section: Introductionmentioning
confidence: 99%
“…The research on gun-related behaviors has not distinguished gendered behaviors, but has indicated that exposure to gun/firearm violence is associated with drugs and alcohol (Garbarino et al 2002;Nielsen and Martinez 2003;Scribner et al 1995;Shepherd et al 2006), as well as illegal activities (Blumstein 1995;Blumstein and Cork 1996;Kacanek and Hemenway 2006). Data from incarcerated women showed that gun carrying among women was associated with selling and use of crack cocaine and other drugs (Kacanek and Hemenway 2006). Spunt et al (1996), in their interviews with female homicide offenders in New York, found that nearly two-thirds of the homicides committed by women were drug related.…”
Section: Introductionmentioning
confidence: 99%